Clean Home, Healthy Family: Unveiling the Link Between Cleanliness and Health - Trenggono, Aisha; Anisa, Isvi; Wahyudi, Zahwa; Khaerunnisa, Nabila; Achdiani, Yani; Ana, Ana (Balai Publikasi Indonesia, 2025)
This work aims to investigate how household cleanliness affects family health from multiple dimensions, including physical, mental, and social aspects. Using a literature study method, this article explores how a clean home environment contributes to disease prevention, emotional stability, and positive family interactions. Findings reveal that maintaining cleanliness such as proper waste disposal, access to clean water, hygienic food preparation, and organized living spaces plays a crucial role in reducing health risks and improving the quality of life. Physically, clean environments prevent infections and promote healthy routines. Mentally, tidy spaces lower stress levels and support emotional well-being by offering a sense of control and comfort. Socially, cleanliness encourages cooperation, respect, and bonding among family members. The results emphasize that cleanliness is not merely about appearance, but is fundamental to sustaining overall family wellness. This study concludes that a consistently clean and well-maintained household significantly enhances the physical, mental, and social health of its members, making it a critical component of family resilience and harmony